Unveiling the threat of crystalline silica on the cardiovascular system. A comprehensive review of the current knowledge - Gurzu, Irina Luciana; Handra, Claudia Mariana; Ghita, Isabel; Otelea, Marina Ruxandra (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThis paper aims to expose the link between occupational exposure to respirable crystalline silica (SiO2) and cardiovascular diseases (CVDs).MethodsA comprehensive review of the literature was conducted, focusing on epidemiological studies that assessed the association between silicosis or SiO2 exposure and CVDs. Specific cardiovascular diseases, such as acute myocardial infarction, arrhythmias, pulmonary hypertension and pericarditis, were also pointed. Biomarkers commonly used in both silicosis and cardiovascular diseases were reviewed to underline the common pathological pathways.ResultsPublished epidemiological data revealed a higher risk of ischemic heart disease, stroke, and hypertension in silica-exposed workers, even at low exposure levels. SiO2 exposure was linked to an increased risk of myocardial infarction, with potential mechanisms involving inflammation and platelet activation. Elevated risk of arrhythmias, particularly atrial fibrillation, correlated with occupational silica exposure. Consistent with the pathological mechanisms supporting the SiO2 exposure—CVDs relationship, biomarkers related to NLP3 inflammasome activation, reflecting oxidative stress, and revealing fibrosis have been presented.ConclusionActual data support the relationship between occupational SiO2 exposure and various CVDs promoting cardiovascular monitoring in silica-exposed workers. Further studies are needed to identify specific/distinctive biomarkers to improve early detection of CVDs in silica exposed workers.